Early and certain Ménière’s disease characterization of predictors of endolymphatic hydrops - Lorente-Piera, Joan; Suárez-Vega, Víctor; Blanco-Pareja, Melissa; Liaño, Gloria; Garaycochea, Octavio; Dominguez, Pablo; Manrique-Huarte, Raquel; Pérez-Fernández, Nicolas (Frontiers in Neurology, 2025)
IntroductionMénière’s disease (MD) is characterized by fluctuating sensorineural hearing loss, tinnitus, aural fullness, and episodic vertigo. Although endolymphatic hydrops (EH) is recognized as a pathognomonic finding, the relationship between clinical presentation, disease duration, and EH severity remains controversial, especially in early-stage MD. This study aimed to determine the impact of disease onset, temporal variables, and clinical phenotypes on EH severity and audiovestibular performance in a cohort with very early MD.MethodsWe evaluated 80 patients diagnosed with certain MD, with symptom duration of less than 3 years. All underwent 3T MRI with 3D-real-IR sequences for EH evaluation, graded using cochlear (HCAFF), vestibular (HVAFF), and volumetric vestibular ratio (RELAFF). Multiple regression and correlation analyses were used to examine relationships between EH and clinical time markers (TD1, TS1, TR1, TR2), phenotypes, onset patterns, and audiovestibular outcomes (PTA, cVEMP, oVEMP, vHIT). Statistical significance was set at p < 0.05.ResultsAll patients exhibited some degree of EH, with 92.5% showing both cochlear and vestibular involvement. No significant correlations were found between time variables and EH severity. However, TS1 and TD1 were significantly associated with PTA in the affected ear (r = 0.277, p = 0.017 and r = 0.318, p = 0.006, respectively). Multinomial regression revealed that vestibular and complete onset patterns predicted more severe vestibular hydrops (HVAFF II and III: p = 0.019 and p = 0.020, respectively). The delayed phenotype was significantly associated with higher RELAFF values (p = 0.032), worse PTA in the affected ear (p = 0.005), and abnormal cVEMP responses (p = 0.002). No associations were found between phenotype or onset form and hydrops in general.DiscussionIn very early MD, clinical time variables do not predict EH severity but correlate with hearing loss severity. The pattern of disease onset significantly impacts vestibular hydrops, whereas age correlates with cochlear EH, likely reflecting age-related hearing vulnerability. Phenotypic differences influence audiovestibular outcomes but not EH presentation. These findings highlight the diagnostic and prognostic utility of early symptom characterization and the need for standardization in defining disease duration in MD research.